Pengenalan Konsep Dasar Bahasa Inggris pada Siswa SD Negeri 72 Kota Bengkulu Melalui English Clinical: Introduction to Basic English Concepts for Elementary Students at SD Negeri 72 Kota Bengkulu Through English Clinical - Nindia Dwi Citra Nindia; Washlurachim Safitri (ABSYARA: Jurnal Pengabdian Pada Masayarakat, 2024)
English is a foreign language that has an important urgency in the current era of globalization. A good command of English can be the key to accessing opportunities, especially in education and works. However, in many elementary schools, English is often sidelined or even replaced by local subjects, raising concerns about the urgency of reform in the Indonesian education system. In response to this challenge, the Ministry of Education has taken the decision to make English a compulsory subject starting from grade 3 of primary school, with an implementation date of 2027/2028. To support this effort, a program called English Clinical was implemented at Elementary School Number 72 Bengkulu City for a period of 2 months involving 30 students. This program aims to improve learners' English competency through the use of creative and innovative teaching methods. Through the English Clinical program, basic English concepts are introduced through learning clubs that adopt learning methods in the form of discussion, question and answer, practice, and assignments, with a focus on a “learning through play” approach. The evaluation results show a very significant improvement in learners' understanding and mastery of English.  The average percentage of correct answers in the final exam ranged from 80% to 100%. Thus, the English Clinical program succeeded in achieving its goal of introducing basic English concepts effectively. The combination of comprehensive learning methods and media brought a positive impact on learners' learning outcomes, confirming the importance of an interactive and fun approach to foreign language learning among children.